Union Density and Varieties of Coverage: The Anatomy of Union Wage Effects in Germany - Alexander C. Lembcke; Karsten Kohn; Bernd Fitzenberger (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2008)
Collective bargaining in Germany takes place either at the industry level or at the firm level; collective bargaining coverage is much higher than union density; and not all employees in a covered firm are necessarily covered. This institutional setup suggests to explicitly distinguish union power as measured by net union density (NUD) in a labor market segment, coverage at the firm level, and coverage at the individual level. Using linked employer-employee data and applying quantile regressions, this is the first empirical paper which simultaneously analyzes these three dimensions of union influence on the structure of wages. Ceteris paribus, a higher share of employees in a firm covered by industry-wide or firm-level contracts is associated with higher wages. Yet, individual bargaining coverage in a covered firm shows a negative impact both on the wage level and on wage dispersion. A higher union density reinforces the effects of coverage, but the effect of union density is negative at all points in the wage distribution for uncovered employees. In line with an insurance motive, higher union density compresses the wage structure and, at the same time, it is associated with a uniform leftward movement of the distribution for uncovered employees. – – Tarifverhandlungen in Deutschland finden entweder auf Branchenebene oder auf Firmenebene statt; die Tarifbindung ist wesentlich höher als der Organisationsgrad der Gewerkschaften; und nicht alle Beschäftigten in einer tarifgebundenen Firma sind tarifgebunden. Diese institutionelle Aspekte legen es nahe, die Effekte der gewerkschaftlichen Macht ? gemessen am Organisationsgrad in einem Arbeitsmarktsegment ? von der Tarifbindung auf Firmenebene und der Tarifbindung auf individueller Ebene zu unterscheiden. Standardergebnisse in der Theorie und empirische Ergebnisse in der Literatur lassen erwarten, dass eine Tarifbindung mit höheren Löhnen und geringerer Lohndispersion einhergeht. Jedoch kann es auch Spillover-Effekte (Übertragungseffekte) aus dem tarifgebundenen Bereich in den nicht tarifgebundenen Bereich geben. Einerseits mögen nicht tarifgebundene Firmen höhere Löhne zahlen, um die Organisation einer Gewerkschaft zu verhindern (?union threat effect?). Andererseits mag die Reduktion der Beschäftigung durch höhere Löhne im tarifgebundenen Bereich zu einem erhöhten Arbeitsangebot im nicht tarifgebundenen Bereich führen. Letzteres mag dort einen Lohndruck nach unten auslösen.
Keywords: J31; J51; J52; 330; Union density; collective bargaining coverage; wage structure; quantile regression; linked employer-employee data; Tariflohn; Tarifpolitik; Gewerkschaftlicher Organisationsgrad; Lohnstruktur; Deutschland